2015
DOI: 10.1002/stem.1938
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interference Targeting of Lnk in Umbilical Cord-Derived Late Endothelial Progenitor Cells Improves Vascular Repair, Following Hind Limb Ischemic Injury, via Regulation of JAK2/STAT3 Signaling

Abstract: The Lnk adaptor protein is a strong negative regulator that affects self-renewal of hematopoietic stem cells and vascular repair in injured tissues. However, the signaling mechanisms through which these proteins influence the vascular regeneration function of endothelial progenitor cells (EPCs) remain unknown. In this study, we investigated the effect of Lnk-targeted small interfering RNA (si-lnk) on the clonogenic proliferative potential and vascular regenerative function of EPCs and the activation of the JAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Our findings indicated that wound repair was significantly enhanced in Lnk-deficient mice as compared with wild-type mice. However, wound repair is a complex biological process that requires several cell types [1, 2], and the Lnk adaptor protein affects various of cell types, including hematopoietic stem cells [24], T cells [25], macrophages [26], EPCs [13, 14], and endothelial cells [27]. Therefore, to focus on one of the populations involved in the wound-healing process, we performed flow cytometry in the wound tissues to search for the recruitment of a specific cell population, and demonstrated that Lnk deficiency in mice specifically increased the recruitment of the EPC population to the injury sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings indicated that wound repair was significantly enhanced in Lnk-deficient mice as compared with wild-type mice. However, wound repair is a complex biological process that requires several cell types [1, 2], and the Lnk adaptor protein affects various of cell types, including hematopoietic stem cells [24], T cells [25], macrophages [26], EPCs [13, 14], and endothelial cells [27]. Therefore, to focus on one of the populations involved in the wound-healing process, we performed flow cytometry in the wound tissues to search for the recruitment of a specific cell population, and demonstrated that Lnk deficiency in mice specifically increased the recruitment of the EPC population to the injury sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that Lnk deficiency in mice promotes EPC kinetics and neovascularization in response to angiogenic cytokines, such as SCF, VEGF, and SDF-1 [13]. In addition, Lnk-deficient EPCs increase the clonogenic proliferation via activation of the JAK-STAT3 signal pathway [14]. These findings strongly support the notion that Lnk deficiency in mice promotes wound repair through the recruitment of EPCs and improves EPC cellular bioactivities, which are initiating steps of vascular repair, which is tightly regulated by the Lnk adaptor protein for cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the survival of engrafted cells and subsequent angiogenesis are considerably insufficient after cell transplantation. 15) In this study, Bai, et al proposed a novel means to overcome this problem, which is pharmacological inhibition of aPKC as a means to recover VEGFR endocytosis and the angiogenic properties of EPCs impaired by mechanical stretch. 8) However, some issues remain to be overcome.…”
Section: Article P356mentioning
confidence: 99%
“…In the immune system, Lnk regulates B cell production by negatively regulating pro-B-cell expansion [11]. Lnk also acts as a negative regulator of stem cell factor (SCF)-c-Kit signaling pathway [1213]. Lnk is positively regulated by IGF-1 in T cells from CHO, suggesting that it functions as both a positive and negative regulator of receptor tyrosine kinase signaling [14].…”
Section: Introductionmentioning
confidence: 99%